Fortress introduction to the Prophets - Hutton, Rodney R., 1948- (Fortress Press, 2004)
Rodney Hutton begins this book by asking five basic questions about Israelite prophecy and the prophetic books. Do the prophetic books witness to a real phenomenon of "prophecy" in Israel? What is the relationship of the "classical" or "writing" prophets to the "pre-classical prophets"? Where do we look for the origins of Israelite prophecy? How do the prophets relate to their culture and society? How does the prophetic collection of writings relate to the legal and historical traditions of Israel? Through literary, social, and theological analysis, the author then introduces the most noted of the Hebrew prophets, including Amos, Hosea, Isaiah, and Micah, with special attention to Jeremiah. --From publisher's description.